White-and-Blue-Collars in a Mill Shutdown - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1968)
This article reviews "White-and-Blue-Collars in a Mill Shutdown" by Felcian F. Foltman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z